2019
DOI: 10.1111/chso.12337
|View full text |Cite
|
Sign up to set email alerts
|

‘Here and There’: Children and Youth’s Perspectives of Borders in Mexico–United States Migration

Abstract: This article explores children’s perspectives regarding migration and family separation on both sides of the Mexico‐U.S. border. ‘Transnational care constellations’1 that connect separated siblings allow children to imagine the other side of the border and to explore their thoughts and perspectives through the lenses of inequality, as well as through a sense of belonging and family. This article presents ethnographic data of families that capture the dynamism of families that are both ‘here and there’ as child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Although possibly not the focus of their agency at the time, children's actions broke the relationship between a shared culture and territory, setting forth ways to do Brazilian culture in US classrooms. Second, children also created avenues of belonging by invoking their transnational social ties, confirming the weight of social relations in children's emergent desire for and sense of belonging (Mand, 2010;Bak and Von Brömssen, 2010;Oliveira, 2019). By invoking loved ones who were "there" and yet very much a part of their lives "here," the children put into perspective the imagined boundedness of nations.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although possibly not the focus of their agency at the time, children's actions broke the relationship between a shared culture and territory, setting forth ways to do Brazilian culture in US classrooms. Second, children also created avenues of belonging by invoking their transnational social ties, confirming the weight of social relations in children's emergent desire for and sense of belonging (Mand, 2010;Bak and Von Brömssen, 2010;Oliveira, 2019). By invoking loved ones who were "there" and yet very much a part of their lives "here," the children put into perspective the imagined boundedness of nations.…”
Section: Discussionmentioning
confidence: 82%
“…Studies that foregrounded the transnational aspects of children’s lives pointed to the importance of social relations in their emergent desire for and sense of attachment to different social groups, places, or ways of being in the world. For example, research showed that transnational migration exacerbated a sense of family membership from children’s perspectives (Dreby and Adkins, 2011; Oliveira, 2019). In Oliveira (2019), children who stayed in Mexico inserted a sense of belonging to their transnational family in their narratives and expressed a strong desire to be part of an imagined family who lived in proximity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our prior analysis of transnational childhoods has centered on the “here” and “there” through the lens of inequality and belonging (Oliveira, 2018, 2019) in this data set the more salient conclusions were the narratives that directly identify the United States as the border. These alternative definitions of the border give us a new framework in which we can contextualize our data.…”
Section: Introductionmentioning
confidence: 90%
“…Though Mexican men and women comprise the flow of migrants, there has been less focus specifically on how children who stay behind in Mexico come to understand the location of where their parents are headed toward. Studies on children in Mexico who have parents that migrated have found that parental migration has implications for children and the overall family structure (Oliveira, 2018(Oliveira, , 2019Boehm, 2011;Dreby, 2010;Gallo, 2014). Children of immigrants in the United States have also been given scholarly attention (Soto and Garza, 2011;Suárez-Orozco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%